Entre a colonialidade e a libertação : uma análise descolonial dos discursos das e sobre as CEB'S - Lopes, Antônio de Lisboa Lustosa (2010)
This thesis is an approach of speeches of and about Basic Ecclesial Communities with a clipping decolonial analysis. The main goal is to identify and show the existence of two types of speeches within the Ceb's, being one spoken and other unspoken, demonstrating the relevance of the actual experience to the construction of a discourse more realistic and consistent with the model of praxis proposed by the Ceb's. Thus, the problem that the thesis has as object is that the supposedly single discourse is actually a discourse utterance while another discourse has been muted. Therefore the no perception of the two discourses is a sign that a type of discourse is presented as the true statement regarding Ceb's. From this, there has been proposed, as specific goals, to identify fundamental themes that appear in the discourses of the Basic Communities and in the discourses of advisors, to problematize these discourses in the comparison amongst themselves and to demonstrate the relevance of places differences in discourse typification. The thesis follows three hypotheses. The main hypothesis is that it is possible that the discourse expressed by advisors as pertaining to the Ceb's may have muted the other unspoken discourse, but it is fulfilled by the people of the Basic Communities. In a secondary level, other hypothesis is that it is possible that underlying the discourse presented,as if it were the only one, there may be differences linked to the place where the actors speakand that, in their turn, influence the way they understand the history. (AU)